MODELING THE EFFECTS OF HEARING LOSS ON NEURAL RESPONSES IN THE COCHLEAR NUCLEUS - VETSIS, STEPHEN (My University, 2009)
Physiological studies of neurons in the dorsal cochlear nucleus (DC ) and ventral cochlear nucleus (VCN) performed by Ma and Young (2006) and Cai et al. (2008) ,respectively, showed the changes in response properties that arise following acoustic trauma. A model of the auditory periphery by Zilany and Bruce (2007) , capable of modeling the effects of acoustic trauma on auditory nerve (AN) fiber responses, was used to simulate inputs to computational models of DCI and VCI cells in order to determine if the changes shown by Cai et al. (2008) and Ma and Young (2006) could be fully explained by changes in the auditory periphery.
DCN cells simulated using the Zheng and Voigt (2006) DCN model receiving AN inputs from an impaired auditory periphery were able to reproduce many of t he types of responses shown by Ma and Young (2006) . Providing impaired AN inputs with compound action potential (CAP) threshold shifts beginning just above DCN cell best frequency (BF) were able to reproduce the tail responses reported by Ma and Young (2006). Type III DCN cells showed class A tail responses whereas, type IV and IV-T DCN cells showed class B tail responses as a result of impaired inputs from the auditory periphery. Type IV-T cells also showed class B-like tails in responses to CAP threshold shifts beginning well below BF. A similar study was performed with VCN cells modeled using the Rothman and Manis (2006c) model. Modeled VCI cells receiving impaired inputs from the auditory periphery did not show most of the behaviors reported by Cai et al. (2008) indicating that the changes in VCN cell reponses following acoustic t rauma are the result of either plastic changes in the brainstem or of features of normal VCI cell responses that are not currently captured by the model.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering